El castillo de la pureza. Concepto de Hogar Mundo y la irrupción de los Nuevos Puritanismos en el contexto de la pandemia de COVID 19 - Gaytán Alcalá, Felipe; Bernal, Ricardo (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
This text tries to show the emergence of a new social dimension identified as Home-World and how through its New Puritanism linked to the religious sphere gain strength that although they resemble the field of neo-conservatisms, but simultaneously distance themselves from them from the field private. The work takes as a reference what happened in Mexico during the COVID 19 pandemic. Methodologically this is an interpretive exercise of a social representation of both the Home-World and what we identify here as New Puritanism based on data, information and events that allow outline this sociological reality.